Senpai Stylo / Prescila Mash Allen - Prescila, Mash Allen (2020)
PMA Sdn Bhd is offering a new innovative product to consumers, which is a two-in-one portable pen known as Senpai Stylo. This business will be situated particularly in Seremban, Neegeri Sembilan. Our company is targeting in supplying pen as pens play a part in our daily routines especially among students and working adults. Besides, the instant lifestyle of today’s society leads us to the idea of creating a pen that gives instant experience with variety of colours to ease writing, drawing or sketching. Senpai Stylo marks a revolution in writing instrumentation as we introduce an innovative premium pen with advance technology that is made of eco-friendly materials. When it comes to choosing a pen, customers would usually buy multiple pens that consist of different colours and tips. Fortunately, Senpai Stylo is made with RGB Color Sensor that scans any colour from the surroundings and replicates it instantly. In other words, one purchase of Senpai Stylo, all colours are accessible compared to only purchasing one or multiple pens with limited colours. It is also refillable, rechargeable and equipped with various tips, which is convenient for everyone to use anytime. Our target markets are college students, businessmen, art designers and lecturers. Our products help to ease students in their studies, convenient for markings and creative learning materials, or as a corporate gift. Senpai Stylo is not a highly expensive but an affordable product. Hence, our products is ideal for urban and sub urban upper middle and middle class people who finds it affordable. Last but not least, our management team are divided into several departments and each department is led by a calibre and professional employee in order to ensure our business runs smoothly with high productivity.